Development of Comprehensive Unattended Child Warning and Feedback System in Vehicle - Norizam, Sulaiman; Kamarul Hawari, Ghazali; M. S., Jadin; Amran, Abdul Hadi; M. S., Najib; Mohd Salmizan, Mohd Zain; Fatimah, Abdul Halim; Suhaimi, Mohd Daud; Nurdiyana, Zahed; Abdul Adam, Abdullah (EDP Sciences, 2017)
In Malaysia, many cases of children get trapped and suffocated in the unattended vehicle were reported and the cases are in increasing trend. It is very surprising that the death caused by the non-moving vehicle keep increasing even though the awareness campaign on the safety of children in non-moving vehicle were carried out by government. The methods that were introduced by previous researchers to detect the present of the children in the unattended vehicle such as the usage of capacitive sensor, microwave sensor, pressure sensor and image sensor have yet to be effective to reduce the number of death in the unattended vehicle. Thus, the research is carried out to provide a comprehensive child detection and feedback system in unattended vehicle by combining the usage of human physiological signals such as voice and body odor with temperature and motion detection systems. The system will integrate all the detection signals and then provide the efficient feedback system by triggering vehicle alarm system and sending message to parents. If no response from parents or no response on vehicle alarm system, the proposed system then will integrate with the existing vehicle security system, ignition system and power window by activating those system. The proposed system is tested successfully to detect the voice, odor and motion of children in vehicle. The project is now at prototype stage and capable to detect the present of voice, odor, motion and temperature in the vehicle accurately and provide the efficient feedback system by sending the message to parents, activating the alarm system and controlling the window movement in order to release the high temperature and toxic gas from the vehicle. The outcome of the project will benefit the security and vehicle manufacturing industry due to the simple design, low cost and easy handling.